Broadening Boards: How Directorships should adapt for challenging times - Singapore Management University (Institutional Knowledge at Singapore Management University, 2012)
"Will good governance lead to greater profitability and business sustainability?" This was the question that framed the lively panel discussion that involved talk on a broad range of issues, from gender diversity to boardroom theatrics.